Perfectly Properly Triable in the United States: Is Extradition a Real and Significant Threat to Foreign Antitrust Offenders? - Kim, Daseul (2008)
Seeking extradition of foreign officers in charge of foreign corporations for trial in the United States is one of the latest policies that the U.S. Department of Justice ( DOJ ) has adopted to enforce U.S. antitrust laws internationally. As a result, the world has become a much riskier place for foreign officers and executives, who, in the past, could practically ignore U.S. antitrust laws and still hide safely behind the protection of their own countries' borders. The DOJ expects this real and significant threat of extradition to incentivize foreign corporate officers to comply with U.S. antitrust laws by altering their conduct, and how they operate their businesses. However, the possible changes effected by the threat of extradition may take a more indirect form than one might suspect. While some of the existing comments and publications seem to tout this new DOJ policy as a universal threat applicable to all foreign officers around the world, there are inherent and practical limitations to international extradition that make it difficult to apply in most cases. This Note will argue that the changes that the DOJ seeks to effect by implementing the new international enforcement policy may take place more indirectly and informally than through the use of international extradition per se